Peningkatan Hasil Belajar Mahasiswa Melalui Pembelajaran Kolaboratif Berbasis Proyek pada Mata Kuliah Geografi Transpotasi dan Pariwisata - Mega Prani Ningsih (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
Project-based collaborative learning is an alternative to 21st century learning. This research aims to examine the application of project-based collaborative learning to improving student learning outcomes, especially in Tourism Geography material. This research is a classroom action research according to Kemmis & McTaggart Theory. Research data was collected through tests and observations. The research instruments were in the form of learning tools, evaluation of learning outcomes, and data collection instruments. The data collection instrument was in the form of question sheets to test student understanding and student activity observation sheets. Data processing techniques in this study were carried out using qualitative and quantitative data analysis. Data validity testing technique uses theoretical triangulation and data source triangulation. The results of this research show that project-based collaborative learning can improve student learning outcomes. These improvements include 1) increasing the criteria for student activity, 2) increasing the percentage of student activity, 3) increasing the lowest score, 4) increasing the highest score, 5) increasing the average score, 6) increasing the number of students who complete their studies, 7) decreasing the number students who have not finished studying, 8) the percentage of learning completeness increases, and 9) the learning completeness criteria increases. This increase in learning outcomes indicates that the project-based collaborative learning model can encourage students to master skills in collaborating and understanding lecture material compared to conventional learning models.